THE EFFECT OF ENTREPRENEUR SOCIAL CAPITAL IN ENTREPRENEURIAL PROCESS OF START-UP DEVELOPMENT - Humam, Muhamad
when many entrepreneurial processes framework identify the role of networking as important part at the start-up development stage, this study have extended the concept of networking and embraced it in the concept of individual social capital of entrepreneurs. However, much of literature on measuring social capital has focused on the quantity of social capital rather than quality made by it. This study will focus and seek to expand the depth and richness of social capital during new venture creation and later identifying the effect of individual social capital in entrepreneurial process. to expand and specify the richness of individual social capital during venture creation, Timmons Model of Entrepreneurial process are used. It considers opportunity, team, and resources as three components for successful new business, and later associate it with Bonding and Bridging and Linking Social Capital of Entrepreneur. The research is mainly expected to provide insight for the business founders and nascent entrepreneurs, help them facing the challenges in starting and running the business, so that they can aware the important of good network and relationship during entrepreneurial process. The focus is to describe how individual social capital of entrepreneur’s networks can affect their own business. This study only considers social capital in individual level and ignore social capital on collective level. This study uses qualitative approach and conducts semi-structured interview with 10 entrepreneurs operating on various industry and various background in Bandung to enhance the Social Capital variety of this study. The Result of This Study shows that individual social capital playing major role during entrepreneurial process. having family and close friends in business, and as well encouragement from family and close friends are strongly associated with successful nascent outcomes. the good social capital of founder’s will be result in better business. We also found as the company grow bigger, the result looks indicate that bridging social capital and linking social capital increasingly become more important, it reveal that bridging social capital connection of entrepreneur’s link it into specific networking and knowledge which may be not available in Bonding Social Capital ties. Overall, Individual social capital exists and affecting entrepreneur’s entrepreneurial process conscious or unconsciously. Suggestion for future research regarding this topic is qualitative study that including personality and environment and relationship or correlation between individual social capital in opportunity, team, and resource aspect of new venture creation.